Study of CoVD19 Pandemic, Financial Ratios, and Macroeconomic Impact on Financial Distress in Indonesian Manufacturing Firms Traded on the Indonesian Stock Exchange - Habibi, Hafid; Utami, Wiwik (FEB - Universitas Lampung, 2022)
The study examined CoV19, financial distress, and other macroeconomic and financial ratios to draw their conclusions. Profitability, liquidity, and leverage were used for financial measures, while inflation and currency exchange rates stood in for macroeconomic indicators. Companies in a financial crisis have lost money for two years, have negative equity, or have a debt-to-asset ratio of more than one. Included in this sample are all 186 manufacturing firms trading on the Indonesia Stock Exchange between 2017 and 2020. From 2017 to 2020, 482 businesses were observed during course time, and the sample was chosen randomly. Logit regression was used to analyze the data. No correlation was found between financial distress and variables like the COVID-19 epidemic, inflation, or currency exchange rates. profitability has a detrimental impact on distress. However, both liquidity and leverage can alleviate distress. Findings are consistent across all segments of the industrial industry. This research shows that financial distress are caused less by general economic conditions and the covid 19 epidemics than by profitability, liquidity, and debt issues.